Environmental policy of the Japan’s and Kazakhstan’s eco-model cities of the future: The case of almaty city government (Journal of Oriental Studies, 2019)
These days it’s common knowledge that air pollution control needs effective actions. The biggest metropolitan city of Republic of Kazakhstan – Almaty city is taken as the base for finding out effective measures of ecomodel cities of the future in Japan. It is given review to the main reforms of the four city administrations regarding environmental policy in the field of transport and logistics. The article analyses conducted measures and reforms aimed at reducing carbon emissions. Realizing projects in Almaty city are the only and newest ones in the republic. Those projects are supposed to be entered to agenda of other big cities and monocities, if they will be found successful and effective. Therefore Almaty city’s environmental policy attracts whole republic’s attention. After the presentation of the main actions of Almaty city policy, it is expected to reveal the best and appropriate measures for the rest big cities and monocities of our republic through making analysis of ecomodel cities of the future in Japan. Accepted by the whole world the Japanese experience will be valuable to the Kazakhstan, which sets its transition into the green economy. Key words: ecomodel city of the future, environmental policy, Japan, Kazakhstan, Almaty, city government, administration.